Recording of Hypertensive Disorders of Pregnancy and Subsequent Cardiovascular Risk Among New Zealand Women - Nikki J Earle; Yeunhyang Choi; Jane Ullmer; Rachel Roskvist; Owen Mugridge; Vanessa Selak; Allan Moffitt; Larry Chamley; Lynn Sadler; Sue Wells; Katrina K Poppe (European Heart Journal - Quality of Care and Clinical Outcomes, 2026)
Abstract Aims Hypertensive disorders of pregnancy (HDP) are established markers of cardiovascular disease (CVD) risk yet are not routinely incorporated into primary prevention. We aimed to (1) assess how HDP is recorded across primary care and national hospitalisation data in New Zealand, and (2) estimate the association between a history of HDP and incident CVD over 5 years. Methods This cohort study used linked health records from the ProCare Primary Health Organisation and national datasets. HDP was identified from Read-coded and free-text general practice records and ICD-10-AM hospital data. Two analyses were undertaken: (1) comparison of HDP recording between primary care and hospital discharge data among women aged 18-64 years; and (2) estimation of 5-year incident CVD risk among women aged 30-64 years without prior CVD. Cox proportional hazards models estimated adjusted hazard ratios (aHRs), incorporating the linear predictor from a national primary prevention CVD risk equation. Results Among 172,328 women aged 18-64 years, a history of HDP was recorded in 4.7% (population-level prevalence), with 91% of this recorded in hospital discharge data only. Over five years, 2,391 women experienced incident CVD events. A recorded history of HDP was associated with a 72% higher CVD risk (aHR=1.72, 95%CI 1.49-1.98). Women with HDP experienced cardiovascular events at younger ages than those without (median 50.2 vs 57.3 years). Conclusion HDP is inadequately recorded in primary care in New Zealand. When documented, it identifies women at significantly higher and earlier CVD risk. Improving HDP documentation in primary care may enable earlier and more equitable CVD prevention.